PENGEMBANGAN PANGKALAN DATA KERAGAMAN SPESIES ANURA DI CAGAR ALAM TELAGA WARNA - Wahyu Prihatini; Sata Yoshida Sri Rahayu; Nida Masyidatul Madyan Al-Adhari (Universitas Pakuan, 2022)
The Telaga Wama Natural Reserve (CATWA) at Bogor Regency, West Java Province is a biodiversity conservation area, however, the changed of some of the area's functions into a Nature Tourism Park can affect the quality of its ecosystem. One approach to evaluate ecosystem quality is through the analysis of Anura species diversity. The continuity of the Anuras eggs and larvae is influenced by the presence of pollutants in the waters. The availability of Anura species diversity database can be an indication of the aquatic ecosystem quality at CATWA. This research was conducted using the Visual Encounter Survey method at five sampling locations in CATWA, namely river, lake, swamp, forest pond, and waterfall. Observations of tadpoles were carried out twice a week, for four weeks, accompanied by physical-chemical measurements of the waters, namely DO, BOD, COD, temperature, pH, depth, and turbidity. The Anura diversity database is made up of a time series, combining of this study result, and previous reports. This study had identified 10 species of tadpoles from six Anura families, namely Dicroglossidae, Megophyridae, Ranidae, Bufonidae, Rhachoporidae and Microhylidae. The level of species diversity is moderate (H'=2.29). Turbidity and water temperature have the highest correlation with species diversity. The water quality in CATWA was relatively good, and able to support the life of Anura. This is also evidenced by the presence of species representatives from all Anura families in Java Island.